Elaboración de queso semi-maduro (andino) con tres diferentes tipos de salami en la planta de lácteos el toril. - Ocaña Veloz, Erika Lilian (2022)
This research was carried out to elaborate on an Andean cheese with three different varieties of salami (garlic, beer, and smoked), adding the different types of salami in different percentages such as 10%, 20%, and 30%, where it is presented which treatment to be analyzed. A sensory analysis was made to evaluate appearance, color, smell, hardness, flavor, and overall impression. Treatment number seven (10% garlic salami) was determined as the best treatment in the sensory analysis. An online survey was conducted to identify the acceptability of the finished product in the market, having optimal results for the product, with an acceptance rate of more than 96%. Once having the best treatment, the microbiological quality of the finished product was evaluated. As a result of the analysis, the product is within the parameters required by INEN regulations, with a maximum index of Enterobacteriaceae identified of less than 10, Staphylococcus aureus a maximum index identified of less than 10, Escherichia coli a maximum index identified as less than 10, Listeria monocytogenes no presence of any bacteria was found, and Salmonella was not present. The level of salami did not affect the other quality tests such as pH, acidity, moisture content, texture, and yield; this should be taken into account that the equipment used should be appropriately calibrated to avoid erroneous results at the time of sampling. The estimated time shelf life of Andean cheese with salami stored at a temperature of 10 °C without cutting its cold chain may increase. A production cost was made, resulting in 150 units to be sold monthly. The record that has been sold annually in Andean cheeses gives us a value of three points fifty, but it will be given to a retail price of four dollars to obtain better profitability.